Age-related risk of major adverse cardiac event risk and coronary artery disease extent and severity by coronary CT angiography: results from 15 187 patients from the International Multisite CONFIRM Study. (May 2014) - Nakazato, Ryo; Arsanjani, Reza; Achenbach, Stephan; Gransar, Heidi; Cheng, Victor Y.; Dunning, Allison; Lin, Fay Y.; Al-Mallah, Mouaz; Budoff, Matthew J.; Callister, Tracy Q.; Chang, Hyuk-Jae; Cademartiri, Filippo; et al.
Abstract: Aims: Prior studies evaluating the prognostic utility of cardiac CT angiography (CCTA) have been largely constrained to an all-cause mortality endpoint, with other cardiac endpoints generally not reported. To this end, we sought to determine the relationship of extent and severity of coronary artery disease (CAD) by CCTA to risk of incident major adverse cardiac events (MACEs) (defined as death, myocardial infarction, and late revascularization). Methods and results: We identified subjects without prior known CAD who underwent CCTA and were followed for MACE. CAD by CCTA was defined as none (0% luminal stenosis), mild (1–49% luminal stenosis), moderate (50–69% luminal stenosis), or severe (≥70% luminal stenosis), and ≥50% luminal stenosis was considered as obstructive. CAD severity was judged on per-patient, per-vessel, and per-segment basis. Time to MACE was estimated using univariable and multivariable Cox proportional hazards models. Among 15 187 patients (57 ± 12 years, 55% male), 595 MACE events (3.9%) occurred at a 2.4 ± 1.2 year follow-up. In multivariable analyses, an increased risk of MACE was observed for both non-obstructive [hazard ratio (HR) 2.43, P < 0.001] and obstructive CAD (HR: 11.21, P < 0.001) when compared with patients with normal CCTA. Risk-adjusted MACE increased in a dose–response relationship based on the number of vessels with obstructive CAD ≥50%, with increasing hazards observed for non-obstructive (HR: 2.54, P < 0.001), obstructive one-vessel (HR: 9.15, P < 0.001), two-vessel (HR: 15.00, P < 0.001), or three-vessel or left main (HR: 24.53, P < 0.001) CAD. Among patients stratified by age <65 vs. ≥65 years, older individuals experienced higher risk-adjusted hazards for MACE for non-obstructive, one-, and two-vessel, with similar event rates for three-vessel or left main ( P < 0.001 for all) compared with normal individuals age <65. Finally, there was a dose relationship of CAD findings by CCTA and MACE event rates with each advancing decade of life. Conclusion: Among individuals without known CAD, non-obstructive, and obstructive CAD are associated with higher MACE rates, with different risk profiles based on age.